Simulation and optimization of perovskite solar cell structure for higher performance - Te, Hui Fang (Nanyang Technological University, 2023)
Perovskite solar cells have sparked a lot of interest in the solar industry in the past years due to their brilliant performance. Perovskite is a low-priced material that offers excellent light absorption, resulting in high power conversion efficiency (PCE). Researchers are constantly discovering new opportunities and ways to increase PCE. In this report, a typical Perovskite solar cell’s device structure has been proposed and the solar cell structure has been optimised by simulating its performance. This is done by varying its structure parameters to achieve higher PCE. The simulation software used in the simulation is OghmaNano. Through OghmaNano, the perovskite solar cell’s operation and performance was simulated by varying each layer’s thickness with different materials. The simulation results have been compared and analysed. A high-performance perovskite solar cell with a high fill factor of 0.81 and a high PCE of 26.53% has been achieved.